Sex role expectations as predictors of career interests among senior secondary school students in Ibadan metropolis (2014)
The cultural practices that seem to over emphasize expectations for male and females have affected human capital development. Not much is known however, the extent to which sex role orientation among senior secondary school students can influence their career interests. This necessitates the study that set to investigate the prediction of career interests using sex role expectations. The survey involved a sample size of 997 comprising of both male and female respondents drawn from 5 private and 5 public schools in Ibadan metropolis. Questionnaires with standardized scales were used for data collection. As hypothesised, sex-role expectations except androgyny, significantly predicted career interests. While femininity significantly predicted' all the six career types, masculinity did not predict realistic career type. It was concluded that sex role expectations play important role in career interests among senior secondary school students. While vocational and career counsellors are encouraged to sensitise students and parents on overcoming social orientations in career choice, future researchers are advised to broaden the scope